Perencanaan Dashboard Untuk Monitoring Kinerja Dosen Menggunakan Metode Noetix dan Rasmussen Pada Fakultas Ilmu Komputer Universitas Pamulang - Hardiansyah Hardiansyah; Afrizal Zein; Emi Sita Eriana (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract The supervisory function of lecturers at the Faculty of Computer Science, Pamulang University is inseparable from teaching, research and community service activities. The increasing number of lecturers and the increasing complexity of the problems they face, demands organizational performance to be further improved. Monitored organizational performance is intended to ensure the achievement of the goals that have been set. Dashboard is a measurement instrument that provides Key Performance Indicator (KPI) information at a glance and in real-time. The dashboard is used as an instrument for monitoring performance, in supporting management needs at both the tactical and operational levels. KPI information is tailored to the needs of its users. The characteristic of this planned dashboard lies in the type of information displayed, as well as the way it is presented, even if only at a glance. Organizational KPI identification is obtained by mapping each KPI in the organization from the viewpoint of the displayed KPI priorities. The method used in designing the dashboard is the Noetix and Rasmussen method, the results of which are the main KPIs of the organization, the information hierarchy and the addition of alerts for the dashboard. Keywords: dashboard, monitoring, KPI, information hierarchy, alerts